Peran teknologi dalam meningkatkan kualitas pendidikan di Indonesia - Sanihah, Mutia (Maliki Interdisciplinary Journal, 2024)
Technology has great potential to change and improve the quality of education in Indonesia. Technological advances in the current global era have greatly influenced the world of education. Global demands require education to continue to adapt technological developments with efforts to improve the quality of education. This study analyzes how various technologies, such as the internet, educational software, and other digital tools, are applied in the educational context in Indonesia. The main focus of this research is to aim to understand the role of technology in the world of education. This research uses qualitative methods by collecting various sources of library data. The results of the research show that the integration of technology in education is able to increase learning effectiveness, expand access to information, and support more interactive and personalized teaching methods.